Predictive factors and treatment outcomes associated with difficult-to-treat rheumatoid arthritis conditions: the ANSWER cohort study - Watanabe, Ryu; Ebina, Kosuke; Gon, Takaho; Okano, Tadashi; Murata, Koichi; Murakami, Kosaku; Maeda, Yuichi; Jinno, Sadao; Shirasugi, Iku; Son, Yonsu; Amuro, Hideki; Katayama, Masaki; et al. (Rheumatology, 2024)
Objectives: To investigate the predictive factors for difficult-to-treat rheumatoid arthritis (D2T RA) and assess the efficacy of biologic DMARDs (bDMARDs) and Janus kinase inhibitors (JAKi). Methods: Retrospective analysis was conducted on data from the ANSWER cohort comprising 3623 RA patients treated with bDMARDs or JAKi in Japan. Multivariate Cox proportional hazards modelling was used to analyse the hazard ratios (HRs) for treatment retention. Results: Of the 3623 RA patients, 450 (12.4%) met the first two criteria of the EULAR D2T RA definition (defined as D2T RA in this study). Factors contributing to D2T RA included age over 75 (compared with those under 65, hazard ratio [HR]=0.46; 95% CI: 0.31, 0.69), higher rheumatoid factor (RF) titres (HR=1.005; 95% CI: 1.00, 1.01), higher clinical disease activity index (HR=1.02; 95% CI: 1.01, 1.03), lower methotrexate dosage (HR=0.97; 95% CI: 0.95, 0.99), and comorbidities like hypertension (HR=1.53; 95% CI: 1.2, 1.95) and diabetes (HR=1.37; 95% CI: 1.09, 1.73). Anti-IL-6 receptor antibodies (aIL-6R, HR=0.53; 95% CI: 0.37, 0.75) and JAKi (HR=0.64; 95% CI: 0.46, 0.90) were associated with fewer discontinuations due to ineffectiveness compared with TNF inhibitors. Oral glucocorticoid usage (HR=1.65; 95% CI: 1.11, 2.47) was linked to increased discontinuation due to toxic adverse events. Conclusion: Younger onset, higher RF titres, and comorbidities predicted D2T RA development. For managing D2T RA, aIL-6R and JAKi exhibited superior drug retention.
CRIS-Team Scopus Importer:2024-09-13
Keywords: anti-interleukin-6 receptor antibodies; difficult-to-treat rheumatoid arthritis; Janus kinase inhibitors; tumour necrosis factor inhibitors